Toward a spinal cord ontology. - Watson, Charles; Sidhu, Amandeep (Academic Press, 2008)
This chapter is a speculative introduction to the creation of a new nomenclatural hierarchy for the spinal cord – an ontology. We have recently been engaged in the construction of mammalian brain ontology based on the avian schema presented by Puelles et al., (2007). During this study, we were struck by the fact that the current spinal cord nomenclature is inconsistent with the developmental subdivisions of the spinal cord revealed by modern molecular genetics (Raff, 2000; Carpenter, 2002; Cohn and Tickle, 1999; Guthrie, 2004; Dasen et al., 2005).